Impaired facial expression recognition in patients with social anxiety disorder: a case-control study. Issue 4 (4th July 2018) - Oh, Kang-Seob; Lee, Woo Hyung; Kim, Sunyoung; Shin, Dong-Won; Shin, Young-Chul; Lim, Se-Won
ABSTRACT: Introduction: The aim of this study was to investigate whether social anxiety disorder (SAD) patients have low emotion recognition accuracy, take longer for emotion recognition and tended to interpret a stimulus more negatively than controls. Methods: Fifty-six SAD patients and 56 healthy controls were participated in this study. We evaluated facial emotion recognition using a computer program in which participants chose one of seven emotions as displayed in each of 55 photographs of faces. We compared the accuracy and reaction times of the patients and controls. We further analysed which emotions were selected in the incorrect answers. Results: SAD patients showed delayed reaction times for all emotions except anger and lower accuracy for fear, surprise, neutrality and happiness compared to controls. After applying Bonferroni correction, only delayed reaction time for surprise and happiness were remain significant. Neutrality was not mistaken for a negative emotion at a higher rate by SAD patients than by controls. Conclusion: This result suggests that the alterations of reaction time and accuracy of emotion recognition of SAD patients, especially in emotions with positive valence, play a more important role than negative bias in the cognitive aspects of SAD.